2021
DOI: 10.14507/epaa.29.4820
|View full text |Cite
|
Sign up to set email alerts
|

Is youth pessimism good for the environment? Insights from PISA 2015

Abstract: In this study, we explore the potential of data from large-scale assessments to provide insights into how students’ environmental knowledge could address the global challenge of environmental threats to humanity and the transition to sustainable development. We analyze data from the 2015 PISA survey to understand the extent to which 15-year old students in 54 countries are aware of these challenges. We find that students’ science activities, self-efficacy and environmental knowledge are positively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
0
0
1
Order By: Relevance
“…The null hypothesis (Ho) is accepted. Contrary to the findings, research has shown that there is a positive relationship between scientific and environmental knowledge and pro-environmental attitudes and behaviors (Pivovarova et al, 2021). However, most past studies have concentrated on the link between environmental awareness and pro-environmental behavior, with limited focus on the relationship between environmental awareness and climate-friendly behavior (Kousar et al, 2022).…”
Section: Challenges Encountered On the Maintenance Of The School Envi...mentioning
confidence: 84%
“…The null hypothesis (Ho) is accepted. Contrary to the findings, research has shown that there is a positive relationship between scientific and environmental knowledge and pro-environmental attitudes and behaviors (Pivovarova et al, 2021). However, most past studies have concentrated on the link between environmental awareness and pro-environmental behavior, with limited focus on the relationship between environmental awareness and climate-friendly behavior (Kousar et al, 2022).…”
Section: Challenges Encountered On the Maintenance Of The School Envi...mentioning
confidence: 84%
“…medioambientales a nivel local y global y pretende ser un aporte a la literatura sobre el tema y un llamado a investigaciones futuras.Por otro lado,Pivovarova et al (2021) exploran datos recabados de evaluaciones a gran escala para proporcionar información sobre cómo el conocimiento de los estudiantes sobre el medio ambiente podría abordar el desafío global de las amenazas ambientales para la humanidad, ayudando a una transición al desarrollo sostenible.En un estudio cuantitativo, los autores analizaron los datos de la encuesta PISA de 2015 realizada por estudiantes de 15 años de 54 países que se encontraban atravesando su escolaridad obligatoria. Intentaron comprender hasta qué punto ellos eran conscientes de estos desafíos.…”
unclassified